Regional Original Revenue Management (PAD) in the Context of Implementation of Development in Malang Regency : (Study on Bappeda Malang Regency) - Hadi Pranoto; Dian Ferriswara; Ika Devy Pramudiana; Sri Kamariyah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to describe and analyze: the management of Regional Original Revenue in Regional Revenue of Malang Regency for regional development, the obstacles faced by the Regional Government of Malang Regency in the Management of Regional Original Revenue and the efforts made as well as the recommendations of the PAD management model. The research is descriptive analysis with the type of research being field research. The data analysis technique uses a technique developed by McNabb (2002), namely Grouping the data according to key constructs, identifying bases for interpretation, developing generalizations from the data, Testing Alternative interpretations and Forming and/or refining generalizable theory from case study. The results of the study show that regional financial management in Malang Regency, especially the Regional Original Revenue (PAD) management policy in Malang Regency, has not been fulfilled because the Regional Government of Malang Regency has not made sufficient and adequate contributions or regional revenues have not been in accordance with what is hinted at in the 2023 budget period. Some of the obstacles faced by Malang Regency in managing local revenue are: a. Limited authority in the collection of Regional Original Revenue. b. Human Resources (HR) of government apparatus to support the mastery, utilization and development of science and technology, supporting facilities and infrastructure, especially to provide convenience for taxpayers and in the development of the management of potential and sources of income need to be improved. Efforts made to increase the Regional Revenue of Malang Regency for the implementation of development are as. Intensifying and extensifying regional taxes and regional levies and exploring the potential of regional revenues to be developed by referring to existing laws and regulations